2018
DOI: 10.1136/jmedgenet-2017-105024
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal, metabolic and skeletal phenotype of Schaaf-Yang syndrome: a comparison to Prader-Willi syndrome

Abstract: This is the first analysis of the hormonal, metabolic and body composition phenotype of SYS. Our findings suggest that there is marked, but not complete overlap between PWS and SYS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 45 publications
(36 reference statements)
2
46
3
Order By: Relevance
“…Literature review yielded 23 articles and 1 Letter to the Editor pertaining to these syndromes, which are summarized in the Preferred Reporting Items for Systematic Reviews (PRISMA) diagram (Figure ) . We include a simplified summary of the patients' symptoms (Table ) and further summaries of all CHS and SYS patients to date (Table S1 in Appendix S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature review yielded 23 articles and 1 Letter to the Editor pertaining to these syndromes, which are summarized in the Preferred Reporting Items for Systematic Reviews (PRISMA) diagram (Figure ) . We include a simplified summary of the patients' symptoms (Table ) and further summaries of all CHS and SYS patients to date (Table S1 in Appendix S1).…”
Section: Resultsmentioning
confidence: 99%
“…Literature review yielded 23 articles and 1 Letter to the Editor pertaining to these syndromes, which are summarized in the Preferred Reporting Items for Systematic Reviews (PRISMA) diagram ( Figure 2). 4,[7][8][9]14,15,[17][18][19][20][21][22][29][30][31][32][33][34][35][36][37][38] We include a simplified summary of the patients' symptoms (Table 1) and further summaries of all CHS and SYS patients to date (Table S1 in Appendix S1). In addition, tissue-specific symptomatic breakdowns for CHS, SYS and PWS are also included (Table S2 in Appendix S1).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Paternal deletions of this region result in Prader-Willi syndrome (PWS, OMIM #176270) [1,2]. It was recently reported that truncating variants in MAGEL2, one of the paternally expressed genes located in this region, caused Schaaf-Yang syndrome (SYS, OMIM #615547) [3][4][5][6][7][8][9][10]. SYS patients present with several symptoms typical of PWS, such as developmental delay, neonatal hypotonia, poor suck that requires special feeding techniques, and excessive weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…SYS patients present with several symptoms typical of PWS, such as developmental delay, neonatal hypotonia, poor suck that requires special feeding techniques, and excessive weight gain. However, they also experience symptoms not typically seen in PWS, including arthrogryposis and autism spectrum disorder (ASD) [3][4][5][6][7][8][9][10]. Truncating variants in MAGEL2 cause severe arthrogryposis with reduced fetal movement resulting in perinatal death [11].…”
Section: Introductionmentioning
confidence: 99%